Does Physical Exercise Improve Resting Autonomic Cardiac Modulation in Overweight and Obese Children and Adolescents? A Systematic Review and Meta-Analysis - Cavenago, Henrique Flore; Venancio, Emerson Jose; Oliveira, Gabriela de; Goldberg, Tamara Beres Lederer [UNESP]; Ramos, Solange de Paula; Silva, Carla Cristiane (Human Kinetics Publ Inc, 2024)
Purpose: The objective of this study was to analyze the impact of interventions with physical exercise on cardiac autonomic modulation of overweight and/or obese children and adolescents. Method: The present systematic review was registered in PROSPERO. Searches were performed in the MEDLINE, CENTRAL, SciELO, Scopus, CINAHL, SportDiscus, LILACS, EMBASE, and Web of Science databases. The methodological quality was assessed using the Cochrane Risk of Bias tool. A meta-analysis was performed using the standardized mean difference. The quality of evidence was rated by the Grading of Recommendations, Assessment, Development, and Evaluation system. Results: From 1866 records identified, 15 randomized clinical trials were included in the systematic review; however, only 4 randomized clinical trials were pooled in the meta-analysis (69 participants in the experimental group and 71 in the control group). The meta-analysis showed a positive effect on the experimental group for the high-frequency power (%; standardized mean difference = 2.22; 95% CI, 1.46-2.98; P < .01), and low-frequency power (%) was reduced after the intervention (standardized mean difference = -1.66; 95% CI, -2.19 to -1.12; P < .01). Conclusion: This study showed that interventions had a positive effect on frequency domain variables of cardiac autonomic modulation in overweight and/or obese children and adolescents. However, more studies with lower heterogeneity and higher quality evidence are needed.
Keywords: pediatric obesity; autonomic nervous system; physical fi tness and sports